PENGARUH DERAJAT KEASAMAN SALIVA TERHADAP PERUBAHAN WARNA SELAMA PERENDAMAN 48 JAM PADA BASIS GIGI TIRUAN LEPASAN THERMOPLASTIC NYLON - , ANAND RETANAM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Thermoplastic nylon which is used as a removable denture base material will show unexpected discoloration after a few months. This discoloration somehow will affect the satisfaction and performance of prosthesis. The purpose of this study is to determine the effect of acidity saliva on color changes for 48 hours on removable dentures base of thermoplastic nylon. This study used 15 thermoplastic nylon square plates which had a size of 10x10x1 mm. The samples were divided into three groups, each group consist of 5 plates thermoplastic nylon. Each group sample was immersed in artificial saliva fluids, group I in the saliva pH 4, group II in the saliva pH 7, and group III in the saliva pH 9, in 48 hours. After soaking in all of the sample groups, and then the color were measured with UV-Vis spectrophotometer pharmaspec, Shimadzu, Kyoto, Japan. Data were analyzed using one-way ANOVA. The result showed that: There was lowest average reading in color changes of thermoplastic nylon after immersion in the saliva pH 4 and there was no significant difference in color changes of thermoplastic nylon after immersion in the saliva pH 4 and pH 7 and pH 9 after 48 hours (p>0.05). The conclusions of this study were there was no significant difference in color changes of thermoplastic nylon after immersion in the saliva pH 4 and pH 7 and pH 9 after 48 hours.